Formation of tourism clusters and models of regional integration development in the city of Samarkand - Janzakov Bekzot Kulmamat oglu (THE INNOVATION ECONOMY, 2026)
This article analyzes the role of the cluster approach in improving the efficiency of tourism services, its economic mechanisms, and potential for practical application. The practical component of the study examines the tourist areas of Samarkand from a geographical and cluster perspective, determining the spatial structure of the historical, transport, scientific and cultural, modern recreational, and airport clusters established in the city. A cartographic analysis demonstrates the mutual integration of the main centers of tourist flows and the infrastructure that serves them. Suggestions are also provided regarding the impact of the tourism cluster system on economic efficiency and ways to strengthen mutually beneficial cooperation between industry participants through organizational and economic mechanisms